Tipologi TOD kawasan Stasiun LRT Sumatera Selatan - Jaya, Meldo Andi; Sary, Reny Kartika; Ramdhani, Muhamad Iqbal (Arsir, 2023)
The rail-based LRT of South Sumatera has been in operation since 2018 and is 23 kilometers long with thirteen stations. This LRT connects Jakabaring district and Sultan Mahmud Badaruddin II airport. Each station's area describes unique characteristics. Therefore, the purpose of this article is to comprehend the various typologies of South Sumatera's LRT station area. Three factors were used to categorize the stations: 1) Land use mix, 2) Density, and 3) Connectivity. And this method is qualitative approach, consisting descriptive approach. The data was gathered from Google Street Map and verified by a field study. This study divided the South Sumatera LRT Station into seven TOD typologies stations.